Calidad de vida en paciente con lesión medular traumático y el cuidado humanizado de enfermería - Morocho Jima, Freddy Miguel; Tinoco Vásquez, Kristhel Esthefania (Machala : Universidad Técnica de Machala, 2021)
Introduction: spinal cord injury according to the WHO is defined as damage caused to the spinal cord due to a sudden trauma to the spine causing a total or partial loss of sensory and / or motor function, having socioeconomic implications that alters the quality of life of patients and their caregivers. The clinical situation in which this pathology occurs is devastating, therefore, due to the loss of independence of the individual and his decrease in functional capacity. For this reason, the objective of this clinical case analysis with bibliographic foundations is to be able to analyze the quality of life of patients with traumatic spinal cord injury, understand the individual, know their feelings and be able to establish a humanized care plan that allows solving basic and functional needs by promoting and protecting health, guaranteeing a favorable environment and a dignified life. Objective: To analyze the quality of life of patients with traumatic spinal cord injury, through bibliographic and observational review; for the application of a humanized nursing care
Introducción: la lesión medular de acuerdo a la OMS se define como un daño provocado en la médula espinal debido a un trauma repentino en la columna vertebral originando una pérdida total o parcial de la función sensorial y/ o motora, teniendo implicaciones socioeconómicas que altera la calidad de vida de los pacientes y sus cuidadores. La situación clínica en la que se presenta esta patología es devastadora por tanto a la pérdida de la independencia del individuo y su disminución de la capacidad funcional. Por ello este análisis de caso clínico con fundamentación bibliográfica es poder analizar la calidad de vida de los pacientes con lesión medular traumática comprender al individuo conocer sus sentimientos y poder establecer un plan de cuidados humanizados que permita solventar las necesidades básicas y funcionales promoviendo y protegiendo la salud, garantizando un ambiente favorable y una vida digna.
Keywords: CUIDADOS HUMANIZADOS; LESION MEDULAR; PROCESO DE ATENCION DE ENFERMERIA